In memory of Professor Dr. Aishah Adam (Dean, Faculty of Pharmacy UiTM, 2009 - 2019) / Mizaton Hazizul Hasan, Nor Amlizan Ramli and Nur Suraya Adina Suratman - Hasan, Mizaton Hazizul; Ramli, Nor Amlizan; Adina Suratman, Nur Suraya (Faculty of Pharmacy, 2024)
It is with deep sadness and a heavy heart that we express our condolences on the passing of Professor Dr. Aishah Adam, an eminent scholar and leader in pharmaceutical education and research.